Study of Fiber Treatment and Water Absorption toward Tensile Stength of Coconut Filtrate/Polyester Composite - Lokantara, Putu; Suardana, Ngakan Putu Gede (Jurnal Energi Dan Manufaktur; Vol 3, No.1 April 2009)
Tapis Kelapa (coconut filter) as natural fiber, in this time it resourches very copius but no longer be exploited off hand andwaste though in fact it used for alternative to be composite. The objective of this research is to investigated tensile strength ofcomposite tapis kelapa as reinforcement and epoxy 7120 and hardener versamid 140 as matrix. The fiber is treated with thechemical NaOH with percentage 0,5%, 1% dan 2% in weight, respectively. This research used coconut-tapis fibre which cutas long as 1cm with 0%,5%,7,5%,10% fiber volume fraction, respectively. Soaking time on the water are 24 hour, 48 hour,98 hour and 196 hour, respectively. For testing of speciment in tensile test with ASTM D3039. The result of this researchshown that the composite with no treatment with NaOH have soak the water better than the composite with treatment NaOH.The average of tensile strength with no treatment NaOH less than with treatment NaOH. The highest strength are reached bycomposite with 10% fraction volume on 48 hour soaking time equal to 52 MPa. While the lowest tensile strength are reachedby composite with 0% fraction volume fibre equal to 16,667 MPa. The average of tensile strength that soak in mineral waterbetter than sea water.
Keywords: Water absorption,Ttensile strength, NaOH